Selection possibility for more efficient nitrogen fixation in cowpea - Barreto, Paulo Diógenes; Nunes, Raimundo de Pontes (Pesquisa Agropecuaria Brasileira, 2014)
Several characters assumed to be related to symbiotic fixation of nitrogen were studied in progenies of 75 selections of two cowpea cultivars, Vigna unguiculata (L.) Walp, in four developmental plant stages. The two cultivars, Seridó and Pitiúba were found to be statistically different to all characters studied. The variation observed among plants in both cultivars suggests that it is possible to select lines within each cultivar for a better efficiency in nitrogen fixation through symbiotic activity, in relation to nodule weight it was possible to identify genotypes of similar behavior and to gather them into groups of the same characteristic pattern. It is suggested that nodule weight is a character of the plant and genetically controlled by it.